OPTIMIZING TOURIST SATISFACTION AT MOJOKERTO'S PACET SPECIAL MARKET THROUGH LOCATION, ATTRACTION AND SOCIAL MEDIA PROMOTION - Ardi Dwi Aditya; Sri Andayani; Ute Chairuz M. Nasution (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This research aims to examine the influence of location, attractiveness and social media promotion on tourist satisfaction at Pasar Keramat Pacet, Mojokerto. Indonesia, with more than 17,540 islands and diverse cultural riches, is a popular tourist destination. In the first semester of 2023, 433.57 million domestic trips were recorded, with East Java contributing 116.7 million visits. Mojokerto Regency, especially Kramatjetak Village in Pacet District, has interesting tourism potential such as "Kramat Market". This research uses quantitative methods with Multiple Linear Regression Analysis. Data was obtained from 108 respondents via e-questionnaire. The research results show that Location, Attraction and Social Media Promotion have a positive and significant effect on tourist satisfaction, both partially and simultaneously, with a determination value of 34.2%. The remaining 65.8% is influenced by other factors such as product quality, word of mouth, service quality and price.